Studi Analisis Susut Energi Listrik Non Teknis dengan Cara Optimalisasi Peremajaan KWH Meter Pascabayar 1 Phasa di PT. PLN (Persero) ULP Painan - Ridal, Yani (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Loss is the amount of energy lost in the process of distributing electrical energy from the substation to consumers. PT PLN (Persero) ULP Painan losses in the second trimester of 2022 are cumulative with a total value of 3,627,350 kWh. Meanwhile, non-technical losses contributed a total kWh with a value of 841,032 kWh. Therefore, it is necessary to optimize the replacement of kWh meters to reduce non-technical losses by forming an independent replacement team and implementing a routine kWh meter replacement schedule, evaluating Subscription Data that Needs Attention (DLPD) to get Work Orders (WO) that are right on target, establishing communication. both with internal parties (Outsourced Personnel) to obtain accurate WO and implement the SOP for replacing kWh meters in the field. After efforts to optimize kWh replacement, the total loss for the third semester of 2022 was 273,096 kWh, a decrease of 567,936 kWh from the second trimester of 2022. If converted into Rp. 818,324,136 for the second trimester of 2022 while for the third trimester of 2022 Rp. 265,722,408 and savings of Rp. 552,601,728.00. The reduction in non-technical losses above was contributed by the achievement of kWh meter replacement of 49,140 kWh. Saving rupiah obtained from obtaining a kWh meter replacement of Rp. 47,813,220.00, therefore efforts to reduce non-technical losses by optimizing kWh meter replacement can be said to help reduce non-technical losses